Polarized M2 macrophages in dogs with visceral leishmaniasis - Moreira, Pamela Rodrigues Reina [UNESP]; Fernando, Filipe Santos [UNESP]; Montassier, Hélio José [UNESP]; André, Marcos Rogério [UNESP]; de Oliveira Vasconcelos, Rosemeri [UNESP] (Elsevier, 2016)
The objective of the present study was to analyze the skin (nasal surface and ear regions), lymph nodes (popliteal and pre-scapular), spleen and liver of dogs with visceral leishmaniasis (VL), in order to investigate the relationship between the parasite load measured as DNA copy number of Alpha gene of DNA polymerase of Leishmania infantum by quantitative PCR and the number of M2 macrophages by immunohistochemistry. A set of 29 naturally infected dogs from an endemic area for VL were sampled and another set of six dogs negative for VL and from a non-endemic area were analyzed as the control group (C). The spleen presented the highest number of Leishmania DNA copies, with significant differences between the groups G1 and G2 (with and without skin lesions, respectively). The M2 phenotype immunostaining predominated among the macrophages in granulomas and inflammatory infiltrates of samples from the skin, lymph nodes and spleens examined. The presence of M2 macrophages in dogs from infected group differed significantly from the control group, in all organs analyzed, excepted liver. The highest proportion of M2 macrophages coincided with the highest parasitism loads found in more susceptible organs of VL dogs, even in the skin, considered a more resistant organ, while the liver showed low parasitism load and low immunostaining for M2 macrophages with no significant differences between infected and negative groups. It was concluded that the predominance of M2 phenotype in VL dogs favored the multiplication of Leishmania infantum in organs of dogs that are more susceptible to Leishmania infection, as skin, lymph nodes and spleen.
Keywords: Dogs; Leishmania infantum; Phenotype phagocytes